Using the Public Open Space Attributable Index tool to assess children's public open space use and access by independent mobility. Issue 2 (4th March 2017) - Chaudhury, M.; Oliver, M.; Badland, H.; Garrett, N.; Witten, K.
Abstract : This study examined associations between public open space (POS) attributes and children's use, and independent mobility to, POS in Auckland, New Zealand. Overall 240 children aged 9–12 years and their parents/caregivers participated. Data were sourced from child travel diaries and parent telephone interviews. The Public Open Spaces Attributable Index (POSAI) assessed POS quality and quantity. Associations were examined between age, sex, ethnicity, parental licence of freedom score, and POSAI with: (1) child trips to POS and (2) independently mobile trips to POS. Children made a total of 68 trips to POS over a seven-day period; 35 of these were independently mobile. Child ethnicity was related to child trips to POS. Independent trips to POS differed by ethnicity and parental licence of freedom. This research utilised a new tool, the POSAI, to examine associations of POS use and independent mobility in children living in urban neighbourhoods.